Inovasi Bahan Ajar E-Learning berbasis Problem Solving berbantuan Moodle - Beslina Afriani Siagian; Christina Sitepu; Nurhayati Sitorus (Jurnal Pendidikan Edutama, 2023)
Abstract: The objectives of this study: 1) measure the feasibility, practicality and effectiveness of e-learning teaching materials through Moodle, 2) measure the achievement of MBKM learning through e-learning teaching materials, 3) achieve the seventh main performance indicator in terms of creating collaborative and participatory classes. The method used in this study is the research and development method based on the 4-D model (Four D Model) which consists of four stages, namely the define stage, the design stage, the develop stage and the disseminate stage. . Data collection techniques were carried out by preparing teaching materials and validating teaching materials by five expert validators. The sampling method used was simple random sampling technique in semester 3 students of FKIP HKBP Nommensen University as many as 75 students and three lecturers as research subjects. Feasibility is reviewed from 3 aspects, namely: valid, effective and practical. With the validation results by the media validator, a score of 75.35% is included in the quite valid category. E-learning validation by the material validator obtains an average score of 87.25% which is in the very valid category. E-learning validation by the language validator obtained an average score of 78.40%, which is in the quite valid category. Moodle-assisted problem solving-based e-learning teaching materials are said to be effective in use which is obtained from the results of the percentage of students who complete reaching 78.80%. E-learning teaching materials based on Moodle-assisted problem solving are said to be practical to use which is obtained from the results of the average percentage score of the overall questionnaire 75.50% included in the practical criteria. Keywords: Teaching Materials; E-Learning; Moodles; MBKM; Problem Solving   Abstrak: Tujuan penelitian ini:1) mengukur kelayakan, kepraktiasan dan keefektivan bahan ajar e-learning melalui moodle, 2) mengukur ketercapaian pembelajaran MBKM melalui bahan ajar e-learning, 3) mencapai indikator kinerja utama ketujuh dalam hal menciptakan kelas yang kolaboratif dan partisipatif. Metode yang digunakan dalam penelitian ini metode research and development berbasis model 4-D (Four D Model) yang terdiri dari empat tahap, yakni tahap pendefinisian (define), tahap rancangan (design), tahap pengembangan (develop) dan tahap penyebaran (disseminate). Teknik pengumpulan data dilakukan dengan menyiapkan bahan ajar dan memvalidasi bahan ajar oleh lima validator ahli. Metode pengambilan sampel yang digunakan adalah dengan tehnik simple random sampling pada mahasiswa semester 3 FKIP Universitas HKBP Nommensen sebanyak 75 siswa dan tiga orang dosen sebagai subjek penelitian. Kelayakan ditinjau dari 3 aspek yaitu: valid, efektif dan praktis. Dengan hasil validasi oleh validator media memperoleh skor 75,35 % masuk dalam kategori cukup valid. Validasi e-learning oleh validator materi memperoleh rerata skor 87,25 % masuk dalam kategori sangat valid. Validasi e-learning oleh validator bahasa diperoleh rerata skor 78,40 % masuk dalam kategori cukup valid. Bahan ajar e-learning berbasis problem solving berbantuan Moodle dikatakan efektif digunakan yang diperoleh dari hasil persentase siswa yang tuntas mencapai 78,80 %. Bahan ajar e-learning Berbasis problem solving berbantuan Moodle dikatakan praktis digunakan yang diperoleh dari hasil persentase rerata skor kuesioner keseluruhan 75,50 % masuk dalam kriteria praktis. Kata Kunci: Bahan Ajar; E-Learning; Moodle; MBKM; Problem Solving